The compartmental restriction of cerebellar interneurons - Consalez, G. Giacomo; Hawkes, Richard (Frontiers in Neural Circuits, 2013)
The Purkinje cells (PC's) of the cerebellar cortex are subdivided into multiple different molecular phenotypes that form an elaborate array of parasagittal stripes. This array serves as a scaffold around which afferent topography is organized. The ways in which cerebellar interneurons may be restricted by this scaffolding are less well-understood. This review begins with a brief survey of cerebellar topography. Next, it reviews the development of stripes in the cerebellum with a particular emphasis on the embryological origins of cerebellar interneurons. These data serve as a foundation to discuss the hypothesis that cerebellar compartment boundaries also restrict cerebellar interneurons, both excitatory [granule cells, unipolar brush cells (UBCs)] and inhibitory (e.g., Golgi cells, basket cells). Finally, it is proposed that the same PC scaffold that restricts afferent terminal fields to stripes may also act to organize cerebellar interneurons.